353 Correlation in cervical cytology, colposcopy and histopathology for detection of pre-malignant lesion of cervix: a study from western rajasthan. (18th September 2019) - Singh, P; Gothwal, M; Yadav, G; Ghuman, N; Elhence, P
Abstract : Objectives: To find out correlation between cervical cytology, and colposcopy in diagnosing premalignant lesions of cervix. To find out correlation in colposcopy and histopathology in detecting premalignant lesion of cervix. Methods: A retrospective study was carried out in OBGYN department over a period of 2 years. Data were retrieved from the departmental records and hospital information system. Inclusion criteria: screen positives who underwent colposcopy and directed biopsy between the age of 21–70 years. Exclusion criteria: Screen positives who did not have colposcopy or where biopsy were not done were excluded. Pregnant women were excluded. These cases were then analysed for sensitivity and specificity in detecting premalignant lesion taking histopathology as gold standard Results: Total of 122 cases were retrieved who fulfilled inclusion criteria, 2 cases were excluded as the biopsy report was inconclusive. Good correlation was observed between colposcopy and histopathology with a sensitivity of 90% and specificity of 98.7%. Cervical cytology and colposcopy showed poor specificity of 58%, and cytology and histopathology had specificity of 62%. Discordance between cytology and colposcopy was seen in 35% of cases. Conclusions: Cervical cytology has a poor specificity for detecting premalignant lesion of cervix as compared to colposcopy and histopathology. A well done colposcopy aids significantly in targeting the tissue precisely for identifying premalignant lesion.